ДОЛЖНОСТ ЗА ЗБОРУВАЊЕ НА ВИСТИНАТА ВО ПАРНИЧНАТА ПОСТАПКА - Rakočević, Milka (Правен Факултет „Јустинијан Први“ во Скопје, 2021)
Procedural powers are not only provided by the law so that the sought legal protection could be provided to the litigants who addressed the court for adjudication in certain legal case, but also for the reason of protecting the legal order. Having in mind the social function that is carried out through the civil procedure, the litigants are obliged to act and behave loyally within the court system of legal protection and to use their procedural right conscientiously. Taking in consideration the broad concept of conscientious use of procedural right and powers, three types of duties are set in front of the litigants: 1) conscientious use of procedural rights, 2) the duty to tell the truth and 3) not to abuse their procedural rights. The subject matter of this article is the duty of telling the truth in civil procedure. The article is focused on analyzing certain questions that are related to the essence of this procedural duty and legal responsibility, taken in broaden context.
Keywords: civil procedure, abuse of procedural rights, duty to tell the truth